2015
DOI: 10.1088/1367-2630/17/9/093040
|View full text |Cite
|
Sign up to set email alerts
|

Flow-driven two-dimensional waves in colonies of Dictyostelium discoideum

Abstract: Dictyostelium discoideum (D.d.) is a valuable model organism to study self-organization and pattern formation in biology. Recently we reported flow-driven waves in experiments with uniformly distributed populations of signaling amobae, D.d., and carried out a theoretical study in a onedimensional model. In this work, we perform two-dimensional numerical simulations using the wellknown Martiel-Golbeter model to study the effect of the flow profile and intrinsic noise on the flowdriven waves. We show that, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…We attribute this difference to the smaller advection speeds at the boundary layer which are enough to destabilize the whole system. This phenomenon was also observed in some preliminary simulations using a parabolic advection flow, 21 where the advection flow velocity is much smaller in a wider region, thus making the instability range of existence much larger.…”
Section: -Dimensional Resultssupporting
confidence: 66%
“…We attribute this difference to the smaller advection speeds at the boundary layer which are enough to destabilize the whole system. This phenomenon was also observed in some preliminary simulations using a parabolic advection flow, 21 where the advection flow velocity is much smaller in a wider region, thus making the instability range of existence much larger.…”
Section: -Dimensional Resultssupporting
confidence: 66%
“…This differential transport of extracellular cAMP induced macroscopic wave trains that had a unique period and propagated with a velocity proportional to the imposed flow velocity downstream. This behavior was studied theoretically [ 16 , 17 ] using the two-component reaction-diffusion model proposed by Martiel-Goldbeter [ 18 ] for the production and relay of cAMP. While the theoretical results could explain much of the experimental observations, there were still open questions regarding the generation of a self supporting wave train at the inlet of the microfluidic channel and only small flow rates of up to 5 mm/min were studied.…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous media, swimming patterns of cells that consist of pulling, pushing, gliding, scrawling, imply that cells interactions with fluids constituents may lead to a variety of spatio-temporal patterns. Experimental and theoretical evidence showed that bacteria are collectively transported through wavy structures like solitary pulses [18][19][20][24][25][26][27][28][29][30]. Furthermore, other experimental findings suggest that hydrodynamic interactions coupled to the chemoattractant concentration gradient may guide traveling bands of bacteria at a constant speed [18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…Besides the importance of chemotaxis in the cellular realm where it plays a major role in fertilization [2][3][4], intercellular communication [5,6], wound repair [2,3], and pattern formation [3,7], it has also been reported in animal and insect ecology [4], large scale collective behavior [1,[8][9][10][11][12][13][14] and synchronization processes [5,8]. Though the literature is well furnished when it comes to chemotaxis, the various issues associated with a combination of chemical and mechanical constraints cells might feature in their natural habitats has just recently started receiving attention [10,[12][13][14][15][16][17][18][19][20][21][22]. It is known that the latter interactions may lead to interesting holistic dynamical behaviors that to the best of our knowledge remain to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation